Acute rhabdomyolysis and inflammation. Issue 4 (17th March 2015) - Hamel, Yamina; Mamoune, Asmaa; Mauvais, François‐Xavier; Habarou, Florence; Lallement, Laetitia; Romero, Norma Beatriz; Ottolenghi, Chris; de Lonlay, Pascale
Abstract: Rhabdomyolysis results from the rapid breakdown of skeletal muscle fibers, which leads to leakage of potentially toxic cellular content into the systemic circulation. Acquired causes by direct injury to the sarcolemma are most frequent. The inherited causes are: i) metabolic with failure of energy production, including mitochondrial fatty acid ß‐oxidation defects, LPIN1 mutations, inborn errors of glycogenolysis and glycolysis, more rarely mitochondrial respiratory chain deficiency, purine defects and peroxysomal α‐methyl‐acyl‐CoA‐racemase defect (AMACR), ii) structural causes with muscle dystrophies and myopathies, iii) calcium pump disorder with RYR1 gene mutations, iv) inflammatory causes with myositis. Irrespective of the cause of rhabdomyolysis, the pathology follows a common pathway, either by the direct injury to sarcolemma by increased intracellular calcium concentration (acquired causes) or by the failure of energy production (inherited causes), which leads to fiber necrosis. Rhabdomyolysis are frequently precipitated by febrile illness or exercise. These conditions are associated with two events, elevated temperature and high circulating levels of pro‐inflammatory mediators such as cytokines and chemokines. To illustrate these points in the context of energy metabolism, protein thermolability and the potential benefits of arginine therapy, we focus on a rare cause of rhabdomyolysis, aldolase A deficiency. In addition, our studies on lipin‐1 (LPIN1) deficiency raise the possibility that several diseases involved in rhabdomyolysis implicate pro‐inflammatory cytokines and may even represent primarily pro‐inflammatory diseases. Thus, not only thermolability of mutant proteins critical for muscle function, but also pro‐inflammatory cytokines per se, may lead to metabolic decompensation and rhabdomyolysis.